2003
DOI: 10.1097/01.pcc.0000074267.11280.78
|View full text |Cite
|
Sign up to set email alerts
|

Helium-oxygen therapy for pediatric acute severe asthma requiring mechanical ventilation

Abstract: In the pediatric patient with severe asthma requiring conventional mechanical ventilation, helium-oxygen administration appears to be a safe therapy and may assist in lowering peak inspiratory pressure and improving blood gas pH and partial pressure CO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Additional studies have reported similar results of reduced peak inspiratory pressures and improved gas exchange, 117 as well as reduced intrinsic PEEP and work of breathing 112 when heliox mixtures are used during mechanical ventilation.…”
Section: Helioxsupporting
confidence: 52%
“…Additional studies have reported similar results of reduced peak inspiratory pressures and improved gas exchange, 117 as well as reduced intrinsic PEEP and work of breathing 112 when heliox mixtures are used during mechanical ventilation.…”
Section: Helioxsupporting
confidence: 52%
“…Heliox reduces peak airway pressures when used in patients who require mechanical ventilation, presumably by allowing hyperinflated alveoli to decompress during expiration and reducing the functional residual capacity of patients with asthma. 150 The existing evidence does not provide support for the routine use of helium-oxygen mixtures to all ED patients with acute asthma. However, new evidence suggests certain beneficial effects in patients with more severe airway obstruction.…”
Section: Helium-oxygen Mixture (Heliox)mentioning
confidence: 99%
“…Heliox was not administered during mechanical ventilation. Although heliox has been demonstrated to provide benefit during mechanical ventilation in life-threatening pediatric status asthmaticus, the improvement in inflation pressure and PaCO 2 , while statistically significant, was clinically only modest (5). Furthermore, differences in gas characteristics between heliox and airnitrogen mixtures can result in inaccurate measurements of ventilatory variables (6).…”
Section: Medical Managementmentioning
confidence: 96%